1982
DOI: 10.1017/s0025315400044039
|View full text |Cite
|
Sign up to set email alerts
|

Larval and Early Post-Larval Development of Arctica Islandica

Abstract: Mature eggs were stripped from ripe adult specimens of Arctica islandica and exposed to a dilute solution of ammonium hydroxide for various lengths of time before addition of stripped sperm. Larval and early post-larval stages were cultured under experimental laboratory conditions using standard bivalve rearing techniques. Larval cultures were maintained at various controlled temperatures ranging from 8·5 to 14·5 °C. Minimum time to settlement was 32 days at a temperature of approximately 13 °C; at temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…A similar structure has been described in several bivalve families including Articidae (Lutz et al, 1982), Cardiidae (Creek, 1960), Laternulidae (Ansell and Harvey, 1997), Lucinidae (Alatalo et al, 1984;Gros et al, 1997), Pandoridae (Allen, 1961), Pectinidae (Hodgson and Burke, 1988), Semelidae (Hughes, 1971;Frenkiel and Moueza, 1979), Solemyidae Reid, 1986, 1988a;Gustafson and Lutz, 1992), Thyasiridae (Blacknell and Ansell, 1974), and Veneridae (Loosanoff and Davis, 1950;Ansell, 1961). In L. aequizonata, the jelly coat appears to be composed of only one layer whereas in C. orbicularis the jelly coat was composed of an inner layer overlying the vitelline membrane and an outer layer distinguishable using phase contrast .…”
Section: Embryonic Developmentsupporting
confidence: 70%
“…A similar structure has been described in several bivalve families including Articidae (Lutz et al, 1982), Cardiidae (Creek, 1960), Laternulidae (Ansell and Harvey, 1997), Lucinidae (Alatalo et al, 1984;Gros et al, 1997), Pandoridae (Allen, 1961), Pectinidae (Hodgson and Burke, 1988), Semelidae (Hughes, 1971;Frenkiel and Moueza, 1979), Solemyidae Reid, 1986, 1988a;Gustafson and Lutz, 1992), Thyasiridae (Blacknell and Ansell, 1974), and Veneridae (Loosanoff and Davis, 1950;Ansell, 1961). In L. aequizonata, the jelly coat appears to be composed of only one layer whereas in C. orbicularis the jelly coat was composed of an inner layer overlying the vitelline membrane and an outer layer distinguishable using phase contrast .…”
Section: Embryonic Developmentsupporting
confidence: 70%
“…The reduction in copper tolerance to the adult level is gradual and completed when a shell length of about 5 mm is reached (Hoare & Davenport 1994). Sub-lethal effects occur at much lower concentrations; Beaumont et al ( l 9871 found a small but significant reduction in vel~ger shell growth at 20 ppb added copper.…”
Section: Introductionmentioning
confidence: 99%
“…In previous examinations (Le Pennec, 1973Pennec, ,1980Lutz & Hidu, 1979;Lutz et al, 1982;Ramorino & Campos, 1983;, details of hinge structures revealed with scanning electron microscopy proved to be of great value in discriminating between larval bivalves. The simple structure of the larval venerid hinge, however, prohibited positive identification of the studied larvae at taxonomic levels below that of family.…”
Section: Larvaementioning
confidence: 94%
“…The shell length of the prodissoconch I was not significantly different (P>0-05) between the taxa. The ligament pit, indicative of competence for metamorphosis (Lutz et al, 1982),…”
Section: Larvae Chioninaementioning
confidence: 99%